İnas Sanayi-i Nefise Mektebi’nde Heykel Eğitimi ve Bu Okulda Eğitim Almış Heykeltıraşlar: Saime Rezan Ramiz Öker, Sabiha Bengütaş ve Nermin Farukî - ÜSTÜNİPEK, MEHMET; Sokur, Büşra (İstanbul Üniversitesi, 2022)
Bu makalede Tanzimat sonrasında başlayan ve İkinci Meşrutiyet ile ivme kazanan değişim sürecinde kadınların toplumsal kazanımlarına değinilerek özellikle eğitim konusundaki gelişmelere yer verilmiş ve İnas Sanayi-i Nefise Mektebi üzerinde durulmuştur. Okulun Sanayi-i Nefise Mektebi’yle birleşme sürecinden sonrası makalenin kapsamı dışında bırakılmıştır. Buradaki heykel eğitiminin içeriğine değinilerek, Saime Rezan Ramiz Öker, Sabiha Bengütaş ve Nermin Farukî’nin sanatsal etkinlikleri ayrıntılı bir şekilde ele alınmıştır. Kadınların sanat eğitimi almalarını sağlamak ve orta dereceli okullara resim öğretmeni yetiştirmek üzere kurulan bu okuldaki eğitim temelde resim sanatına odaklanmıştır. Ancak okulda eğitimin bir parçası olarak İhsan Özsoy’un eğitim verdiği bir heykel atölyesi de yer almaktadır. Bu makalede okuldaki heykel eğitiminin içeriği saptanmaya çalışılmıştır. Ayrıca, okulda eğitim alarak heykel alanında sanatsal üretim ve etkinlikleriyle daha kalıcı oldukları saptanan üç heykeltıraş seçilmiş olup, bu sanatçıların yaşamları ve çalışmalarının ayrıntılı bir şekilde ele alınması amaçlanmaktadır. Arşiv, süreli yayın ve kaynak taraması ile elde edilen bilgiler doğrultusunda İnas Sanayi-i Nefise Mektebi’nde heykel eğitiminin ayrı bir disiplin olarak ele alınmadığı ve resim eğitimini destekleyici bir atölye düzeni kapsamında gerçekleştiği anlaşılmaktadır. Bu atölyede eğitim alarak heykel alanında etkinlik gösteren isimler arasında, üretim ve etkinliklerinde devamlılığı sağlamış bu sanatçı kadınların; sanat pratiklerini ortaya koyarak, sanat tarihi yazımında eksik kalan konumlarını belirlemek amaçlanmaktadır.

In this article, the social gains of women were mentioned in the process of change that started after the Tanzimat and gained momentum with the Second Constitutional Monarchy, and especially the developments in education were given and the İnas Sanayi-i Nefise Mektebi was emphasized. After the school's merger process with Sanayi-i Nefise Mektebi, it was left out of the scope of the article. By referring to the content of the sculpture education here, the artistic activities of Saime Rezan Ramiz Öker, Sabiha Bengütaş and Nermin Faruki are discussed in detail. The education in this school, which was established to enable women to receive art education and to train art teachers for secondary schools, mainly focused on the art of painting. However, as a part of the education, there is also a sculpture workshop where İhsan Özsoy teaches. In this article, the content of sculpture education in the school has been tried to be determined. In addition, three sculptors who were found to be more permanent with their artistic production and activities in the field of sculpture by studying at school were selected, and it is aimed to discuss the lives and works of these artists in detail. In line with the information obtained through archives, periodicals and resource scanning, it is understood that sculpture education in İnas Sanayi-i Nefise Mektebi was not considered as a separate discipline and was carried out within the scope of a workshop order that supports painting education. Among the names who were active in the field of sculpture by receiving education in this workshop, these artist women who ensured the continuity in their production and activities; It is aimed to determine the missing positions in art historiography by revealing art practices.

In this article, the social gains of women were mentioned in the process of change that started after the Tanzimat and gained momentum with the Second Constitutional Monarchy, and especially the developments in education were given and the İnas Sanayi-i Nefise Mektebi was emphasized. After the school's merger process with Sanayi-i Nefise Mektebi, it was left out of the scope of the article. By referring to the content of the sculpture education here, the artistic activities of Saime Rezan Ramiz Öker, Sabiha Bengütaş and Nermin Faruki are discussed in detail. The education in this school, which was established to enable women to receive art education and to train art teachers for secondary schools, mainly focused on the art of painting. However, as a part of the education, there is also a sculpture workshop where İhsan Özsoy teaches. In this article, the content of sculpture education in the school has been tried to be determined. In addition, three sculptors who were found to be more permanent with their artistic production and activities in the field of sculpture by studying at school were selected, and it is aimed to discuss the lives and works of these artists in detail. In line with the information obtained through archives, periodicals and resource scanning, it is understood that sculpture education in İnas Sanayi-i Nefise Mektebi was not considered as a separate discipline and was carried out within the scope of a workshop order that supports painting education. Among the names who were active in the field of sculpture by receiving education in this workshop, these artist women who ensured the continuity in their production and activities; It is aimed to determine the missing positions in art historiography by revealing art practices.
Sculpture Education at Inas Sanayi-i Nefise Mektebi and Sculptors Who Studied There: Saime Rezan Ramiz Oker, Sabiha Bengutas & Nermin Faruki
Keywords: İnas Sanayi-i Nefise Mektebi; Rezan Ramiz Öker; Sabiha Bengütaş; Nermin Farukî; Heykel Eğitimi